An Investigation of Hayes and Wheelwright’s Practices: Empirical Evidence from The Indonesia’s Oil and Gas Industry - Wakhid Slamet Ciptono (Jurnal Siasat Bisnis, 2006)
The research extracts sixty seven Hayes and Wheelwright’s practices from the Hayes and Wheel-wright’s six principles. These items formed the basis of a questionnaire sent to over 2800 managers at the SBUs level in the Indonesia’s oil and gas companies. The empirical result indicates that All Hayes and Wheelwright’s six principles collectively have positive impact on an overall construct that may be termed world-class company (WCC). Result also points out that Hayes and Wheelwright’s six principles can be reduced into four meaningful factors) of world-class company—as operations strategies—for the Indonesia’s oil and gas industry— Workforce skills and capabilities, Management technical competence, Competing through quality, and Workforce participation. These meaningful factors of WCC were shown to be reliable and valid, and offer new insights into the understanding of operations strategy implementation in an oil and gas industry.Based on the oil and gas managers (the SBU level), operations strategies (four meaningful factors of WCC) can be viewed as the effective use of production and operations capability and technology for achieving business and corporate goals. Operations strategy, therefore, is to help a company’s operations organization define the common ground where it can play a proactive and collaborative role with other company functions or cross-functional relationships (Hayes et al., 1996).  Oil and gas managers in Indonesia can use these meaningful factors in concert with other critical qual-ity management practices to help them in there word-class company initiatives. Researchers can also use these factors to build structural model linking such factors to various organizational performance measures (i.e., Critical Success Factors of TQM, Operational Excellence, Six Sigma Quality Management, and Good Corporate Governance).Keywords: Hayes and wheelwright’s six principles, Hayes and Wheelwright practices, World-Class Company.